Origins, evolution and future of global development cooperation: The role of the Development Assistance Committee (DAC) - Gerardo Bracho; Richard H. Carey; William Hynes; Stephan Klingebiel; Alexandra Trzeciak-Duval (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Since its foundation in 1961, the OECD Development Assistance Committee (DAC) - nerve centre of the aid effort of the 'rich' countries - has played a central role in the PostWar aid system. This book traces the history of the institution and reflects on its future. How intense diplomacy led to the creation of the OECD itself and the DAC is disclosed here for the first time. How the DAC works, how it shaped development finance by defining and measuring Official Development Assistance (ODA), and how it has pursued its founding mission to increase the volume and effectiveness of aid, are key to the story. The end of the Cold War brought on major aid fatigue. In response, the DAC proposed human development goals that eventually became the UN Millennium Development Goals (MDGs). It also prioritised policy frontiers such as gender equality, fragile states, sustainable development and policy coherence. More recently, the universal 2030 Sustainable Development Goals (SDGs) have succeeded the MDGs. China has become a leading source of development finance, population in SubSaharan Africa is set to double to 2 billion by 2050 out of a world total of 10 billion, and 'global public bads' such as climate change and worldwide pandemics are putting not only development but our civilisation at risk. In this environment of unprecedented challenges and contested cooperation, the DAC seeks its place in the evolving global development architecture.
Keywords: 330; Entwicklungshilfe; Entwicklungspolitik; Entwicklungsorganisation; Welt